On the syntaxonomy of segetal communities of the Kherson region (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In the article the results of syntaxonomical, cluster and ordinational analysis of segetal communities of the orchards, vineyards and sunflower’s fields of the Kherson region are given. Syntaxonomical scheme includes 6 associaions, 5 alliances, 2 orders of the class Stellarietea mediae.
Keywords: segetal community, syntaxonomy, Stellarietea mediae, ordinational analysis, Kherson region.